Lactate Improves Prediction of Short‐Term Mortality in Critically Ill Patients With Cirrhosis: A Multinational Study. Issue 1 (17th December 2018) - Drolz, Andreas; Horvatits, Thomas; Rutter, Karoline; Landahl, Felix; Roedl, Kevin; Meersseman, Philippe; Wilmer, Alexander; Kluwe, Johannes; Lohse, Ansgar W.; Kluge, Stefan; Trauner, Michael; Fuhrmann, Valentin
Abstract : Lactate levels and lactate clearance are known predictors of outcome in critically ill patients in the intensive care unit (ICU). The prognostic value of lactate is not well established in liver cirrhosis and acute‐on‐chronic liver failure (ACLF). The aim of this study was to assess the prognostic value of lactate levels and clearance in critically ill patients with cirrhosis. Patients with cirrhosis admitted to the ICU were studied at the University Medical Center Hamburg‐Eppendorf (n = 566, derivation cohort) and the Medical University of Vienna and the University Hospitals Leuven (n = 250, validation cohort). Arterial lactate was measured on admission and during the first 24 hours. Patients were followed for 1 year and outcome was assessed. Admission lactate was directly related to the number of organs failing and to 28‐day mortality (area under receiver operating characteristic [AUROC] 0.72; P < 0.001). This also applied to lactate follow‐up measurements after 6, 12, and 24 hours ( P < 0.001 for all, AUROC > 0.70 for all). Lactate clearance had significant predictive ability for 28‐day mortality in patients with elevated serum lactate ≥5 mmol/L. Admission lactate and 12‐hour lactate clearance (in patients with admission lactate ≥5 mmol/L), respectively, were identified as significant predictors of 1‐year mortality, independent of Chronic Liver Failure Consortium acute‐on‐chronic liver failure score (CLIF‐C ACLFs). A lactate‐adjusted CLIF‐C ACLFs was developed (CLIF‐C ACLFsLact ), which performed significantly better than the original CLIF‐C ACLFs in prediction of 28‐day mortality in the derivation and validation cohort. Conclusion: Lactate levels appropriately reflect severity of disease and organ failure and were independently associated with short‐term mortality in critically ill patients with liver cirrhosis. Lactate is a simple but accurate prognostic marker, and its incorporation improved performance of CLIF‐C ACLFs significantly.